2013
DOI: 10.1021/jp406412f
|View full text |Cite
|
Sign up to set email alerts
|

Excited Electronic State Mixing in 7-Azaindole. Quantitative Measurements Using the Stark Effect

Abstract: Stark effect measurements of the +280 cm(-1) vibronic band at ∼286 nm in the high resolution S1-S0 fluorescence excitation spectrum of 7-azaindole (7AI) in a molecular beam show that the permanent (electric) dipole moment (PDM) of the upper state vibrational level reached in this transition is 4.6 D, twice as large as the PDM of the zero-point level of the S1 state. This large difference is attributed to state mixing with a more polar state. EOM-CSSD calculations suggest that this more polar state is σπ* in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…27 In fact, the recent theoretical study using EOM-CCSD theory overestimates this state by 0.7 eV. 20 Given these uncertainties, the SAC-CI calculation is again in reasonable agreement with experiment. The predicted oscillator strengths reveal that 1 L a is more intense than the 1 L b state, as it has been concluded in previous theoretical studies.…”
Section: B Sac-ci Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…27 In fact, the recent theoretical study using EOM-CCSD theory overestimates this state by 0.7 eV. 20 Given these uncertainties, the SAC-CI calculation is again in reasonable agreement with experiment. The predicted oscillator strengths reveal that 1 L a is more intense than the 1 L b state, as it has been concluded in previous theoretical studies.…”
Section: B Sac-ci Resultsmentioning
confidence: 64%
“…27 A recent EOM-CCSD study found the excitation energy of this state as 4.85 eV and the adiabatic excitation energy for this state is calculated as 4.67 eV. 20 By considering the deviations of all these theoretically calculated values from the experimental one, the value obtained using SAC-CI is reasonable.…”
Section: B Sac-ci Resultsmentioning
confidence: 81%
See 3 more Smart Citations